A Melting Pot of Literature and Orature: An Intertextual Analysis of Bosede Afolayan’s Once Upon an Elephant - ADEYANJU, Adewumi Raphael; AJALA, Adeola Toyosi; ADEBAGBO, Adebanjo (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
African writers are products of double heritages, of both the Western education they are exposed to and the immediate cultural environments from where they have appropriated materials for their literary enterprises. There is however the tendency to down play the influence of African oral tradition on African Literature by concentrating on the influence of foreign writings on African literary texts. Recent scholarly works have examined the relationship between works of African writers to establish intertextual relationships among their written texts but paid little attention to the African oral resources as a distinct text on its own right. The study aimed to fill the observed gap by examining the influence of orature on literary texts, specifically, on Bosede Afolayan’s play, Once Upon an Elephant. The study employed both primary and secondary sources of data collection, which involved a close reading and in-depth analysis of the selected primary text and some secondary texts, adopting Intertextual theory as a tool of analysis. Intertextual theory is basically about similarities and differences between presumably related texts. The study made strong case for more intertextual practices among African writers with the recommendation that both creative writers and critics can enrich their works by looking inward, especially their immediate African cultural environment as veritable fount to source materials for their creative enterprises.